(untitled) (European Journal of Marketing and Economics, 2026)
The existence of the crisis makes obvious the fact of predicting the financial position in which will be found an economic unit in the future. This constitutes one of the most important tasks of analysts. Altman Z-Score andQuick Test Kralicek are two very important cumulative indicators, on the basis of which, the analyst is able to give a judgment on the financial situation in which an economic unit is, as regard to the risk of bankruptcy (Altman Z -Score) and difficulty paying (Quick Test Kralicek). By analyzing these two indicators, it was foundthat they are connected with each other and lead us to the same conclusion for entities taken as a sample in this study. Through a statistical analysis (Pearson correlation coefficient) will be shown this connection and the conclusions derived from this analysis. Predicting in time unsatisfactory situations avoids the risk of bankruptcy, which is so much evident nowadays.